2019
DOI: 10.1097/01.aoa.0000603808.91052.ed
|View full text |Cite
|
Sign up to set email alerts
|

The DiPEP Study: An Observational Study of the Diagnostic Accuracy of Clinical Assessment, D-dimer and Chest X-ray for Suspected Pulmonary Embolism in Pregnancy and Postpartum

Abstract: (BJOG. 2019;126(3):383–392) Pulmonary embolism (PE) is a leading cause of maternal mortality during pregnancy and postpartum, therefore symptomatic at-risk women are commonly seen in emergency departments and maternity units to rule out PE. Recommendations regarding diagnosis of PE vary among various professional societies. Recent reviews have not found sufficient evidence to suggest that D-dimer is an effective tool in detecting PE, mainly due to the low prevalence of PE in study subjects. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…were not valid or clinically useful in pregnant and postpartum women. [32][33][34] Seven studies describing social determinants of health and postpartum ED use were included (►Table 4). Five studies were from the United States, one from Canada, and one from Bangladesh and Burkina Faso.…”
Section: D-dimers and Clinical Decision Rules To Address The Likeliho...mentioning
confidence: 99%
“…were not valid or clinically useful in pregnant and postpartum women. [32][33][34] Seven studies describing social determinants of health and postpartum ED use were included (►Table 4). Five studies were from the United States, one from Canada, and one from Bangladesh and Burkina Faso.…”
Section: D-dimers and Clinical Decision Rules To Address The Likeliho...mentioning
confidence: 99%
“…Pregnant patients were excluded from the derivation studies, and relatively few prospective data have been published to validate the tools in this population. 44,45,[48][49][50][51][79][80][81][82] Because those guidelines were published, 3 studies have delivered the first high-quality research on this topic:…”
Section: Clinical Decision Rulesmentioning
confidence: 99%
“…Routine physiologic changes of pregnancy often produce dyspnea, lower extremity edema, and resting tachycardia that mimic signs and symptoms of PE, thereby presenting a challenge for physicians to assess the presence of PE based on clinical factors alone. For example, among pregnant and postpartum women tested for PE in the DiPEP study, those with PE had similar rates of pleuritic chest pain (52%), dyspnea (54%), palpitations (13%), cough (8%), and syncope (5%) compared with women without PE 45 . In that study, variables associated with PE included older age, lower oxygen saturation, lower systolic blood pressure, and temperature; however, these continuous variables often provide little value for distinguishing PE from other common conditions on the basis of physical examination alone.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Goodacre et al 44 used a cohort study augmented by additional confirmed cases of PE from the UK Obstetric Surveillance System. These investigators found that both clinical and D-dimer criteria for further imaging studies showed high sensitivity only at the expense of very low specificity.…”
mentioning
confidence: 99%